The Effect of Variation in SiMn/PS Nanocomposite Composition on Hydrophobic Properties - Sisi Gusti Putri; - Ratnawulan (PILLAR OF PHYSICS, 2021)
Many researches on the synthesis of hydrophobic coatings have been carried out, but in use, the coating is easily scratched, easily damaged by contact with other objects and easy to corrode, thereby reducing the quality of the coating. This can hinder the application of hydrophobic coatings in industry and others. Therefore, it is necessary to develop a hydrophobic coating that is strong and durable and anti-corrosion so that it can improve the quality of a surface. For this reason, research is carried out by mixing a substrate that has anti-corrosion properties such as silica and is hard such as manganese in order to overcome the problems that occurred previously using the spin coating method. The precursor was made by adding 0.5 grams of polystyrene composition, with varying SiMn composition. The coating was carried out using the spin coating method and the calcination temperature was 60°C using an oven for 1 hour. The results of this study from the composition variation showed that the SiMn/PS nanocomposite layer was hydrophobic based on the contact angle test. The largest contact angle at 50%:50% composition.